Autologous blood as a source of platelet gel for the effective and safe treatment of oral chronic graft‐versus‐host disease. Issue 6 (14th March 2018) - Bojanic, Ines; Mravak Stipetic, Marinka; Pulanic, Drazen; Desnica, Lana; Mazic, Sanja; Golubic Cepulic, Branka; Serventi Seiwerth, Ranka; Vrhovac, Radovan; Nemet, Damir; Pavletic, Steven Z.
Abstract : BACKGROUND: Oral chronic graft‐versus‐host disease (cGvHD) impairs oral function and patients' quality of life. Some lesions are refractory to local and systemic immunosuppressive therapy, and new therapeutic modalities are required. The aim of the study was to assess the efficacy and safety of topical application of autologous platelet gel (PG) in patients with oral cGvHD. STUDY DESIGN AND METHODS: PG was prepared from autologous blood and applied on ulcerous lesions using an automated system. The oral cGvHD was assessed using the 273‐point Oral Mucositis Rating Scale (OMRS) prior and after completion of the PG treatment. The overall response to treatment of particular topography expressed as the total score on OMRS was compared to total score on National Institutes of Health cGvHD Oral Mucosal Score (NIH OMS). The pain intensity was measured by the Numeric Pain Rating Scale (NRS). RESULTS: In five patients, 12 autologous blood collections were performed; median 3 (range 1‐3) per patient, and 26 PG applications were performed; median 6 (range 2‐8) per patient. PG applications reduced lesions in oral cGvHD: median OMRS total score was reduced for 43.2% (range 9.6%‐47.3%), and median NIH OMS total score for 27.3% (range 20.0%‐50.0%) from baseline values. Median of pain intensity reduction on NRS scale was 57.1% (range 50%‐100%). No side effects were observed. CONCLUSION: Application of autologous PG in oral cGvHD showed as an efficient and safe treatment option for patients who do not respond to standard local treatment.